Maskulinitas Rapuh di TikTok: Representasi Emosi Lelaki dalam Budaya Siber Gen Z: Fragile Masculinity on TikTok: Representations of Men's Emotions in Gen Z's Cyber Culture - Ahmad Fauzan; Dinda Ayu Rindiyani; Akhmad Tabrani (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The emergence of â€œfragile masculinityâ€ among Gen Z males on TikTok marks a significant cultural shift in emotional expression within digital spaces. This phenomenon is not merely a reflection of personal sentiment but embodies a complex interplay of platform affordances, algorithmic visibility, and symbolic gender performance. This study investigates how emotional expressions by young men on TikTok operate as performative acts influenced by platform logic and techno-cultural norms, contributing to the reconfiguration of digital masculinity.Using a qualitative multimodal content analysis of 30 TikTok videos tagged with emotional labels (e.g., #sadboy, #overthinker), this research integrates discourse analysis, visual semiotics, and user engagement metrics. Findings reveal three key dynamics: (1) emotional performativity is constructed through audiovisual aesthetics and shaped by algorithmic preferences; (2) vulnerability operates as both emotional capital and branding strategy; (3) validation mechanisms embedded in the platform incentivize the commodification of emotional expression.This study underscores how algorithmic governance shapes affective expression and generates gendered visibility. TikTok functions not only as a social media space but as an ideological arena where masculinity is rearticulated through stylized vulnerability. While this challenges traditional hegemonic norms, it also imposes emotional standards dictated by virality and platform capitalism.